2005
DOI: 10.1152/ajpregu.00186.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of PKC in the regulation of gonadotropin subunit mRNA levels: interaction with two native forms of gonadotropin-releasing hormone

Abstract: of PKC in the regulation of gonadotropin subunit mRNA levels: interaction with two native forms of gonadotropin-releasing hormone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…A similar finding with differential involvement of PKC in pituitary adenylate cyclaseactivating peptide-induced SL␣ and SL␤ expression via PLC-dependent mechanisms has been recently reported in the carp pituitary (47). Given that multiple isoforms of PKC have been identified in the fish pituitary, eg, goldfish (48), and some of them, eg, PKC and PKC , are known to have atypical pharmacological properties (49), we do not exclude the possibility that PKC isoforms insensitive to GF109203X might be involved in the PRL responses occurred in the carp pituitary. In our study, Ca 2ϩ imaging also revealed that NKB and NKBRP were both effective in triggering a biphasic Ca 2ϩ rise with an initial peak followed by a shoulder phase in carp pituitary cells.…”
Section: Discussionsupporting
confidence: 80%
“…A similar finding with differential involvement of PKC in pituitary adenylate cyclaseactivating peptide-induced SL␣ and SL␤ expression via PLC-dependent mechanisms has been recently reported in the carp pituitary (47). Given that multiple isoforms of PKC have been identified in the fish pituitary, eg, goldfish (48), and some of them, eg, PKC and PKC , are known to have atypical pharmacological properties (49), we do not exclude the possibility that PKC isoforms insensitive to GF109203X might be involved in the PRL responses occurred in the carp pituitary. In our study, Ca 2ϩ imaging also revealed that NKB and NKBRP were both effective in triggering a biphasic Ca 2ϩ rise with an initial peak followed by a shoulder phase in carp pituitary cells.…”
Section: Discussionsupporting
confidence: 80%
“…These results argue against the possibility that TPA-induced SL gene expression was caused by PKC desensitization. This idea was also supported by the studies using DiC8 (10 M), a nondesensitizing diacylglycerol analog (17) that could mimic TPA stimulation of SL␣ and SL␤ mRNA expression in carp pituitary cells (Fig. 4B, inset).…”
Section: Pacap Induction Of Sl␣ and Sl␤ Mrna Expressionmentioning
confidence: 59%
“…Despite the fact that the rise in SL␤ mRNA levels caused by PACAP could be negated by inhibiting PLC and IP 3 receptors, this stimulatory action was not affected by PKC blockade, suggesting that the PKC component may be uncoupled from PLC-dependent mechanisms leading to SL␤ gene expression. Since PKC isoforms are expressed in the goldfish pituitary in a cell-type specific manner (17) and the atypical isoforms, e.g., PKC and PKC , are known to be insensitive to stimulation by phorbol ester and diacylglycerol (25), it is tempting to speculate that the lack of PKC involvement in PACAP-induced SL␤ (14). These findings raise the possibility that the Ca 2ϩ /CaM-dependent cascades for SL gene expression may be secondarily coupled with the PKA-and PKC-dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the reduction in SL␤ mRNA levels caused by gbSS-28 could be negated by inhibiting PLC and IP 3 receptors, this inhibitory action was not affected by PKC blockade, suggesting that the PKC component may be uncoupled from PLC-dependent mechanisms leading to SL␤ gene expression. Because PKC isoforms are expressed in the goldfish pituitary in a cell type-specific manner (22), the differential regulation of the SL isoforms may result from different components of PKC isoforms expressed in NIL cells. Also, given that IP 3 receptors are Ca 2ϩ channels responsible for intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) release from IP 3 -sensitive Ca 2ϩ stores (11), we should not rule out the possibility that [Ca 2ϩ ] i mobilization may contribute to gbSS-28-inhibited SL gene expression.…”
Section: R764mentioning
confidence: 99%